PENENTUAN PREKURSOR GEMPA BUMI MENGGUNAKAN DATA MAGNETOTELLURIK DI DAERAH PELABUHAN RATU - Noviana Fransiska; Agus Setyawan; Boko Nurdiyanto (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2013)
The research has been done by using data of electromagnetic parameter base on the result of magnetotelluric observation which located in geophysics observation Pelabuhan Ratu. Research of earthquake precursor in order to find out the characteristic of electromagnetic signal by applying spectral analysis ratio method on Ultra Low Frequency (ULF). The data is electromagnetic secondary data from observation result of magnetotelluric and data of Dst index year 2011. The data magnetotelluric is consist of electric component and magneict component. The filtering data is executed by using wavelet method. Result of filtering will be shown as graph ratio of magnetic field and electric field spectral intensity in a time domain. According to the analysis by using spectral density analysis can be found out that the characteristic of ULF signal on frequency 0.01 Hz before earthquake show that there is an increase of value for magnetic polarization and occurred decrease of EM wave impedance value. From the analysis result show an appearance of magnetic polarization anomaly which expected as earthquake precursor and can be seen around 10 – 19 days before the occurrence of earthquake while for the value of EM wave impedance can be seen around 23 – 40 days before earthquake.Keywords : Precursor, Ultra-Low-Frequency, Spectral Density Ratio Analysis, Pelabuhan Ratu